The orientation of the bibliometrics researchers in Indonesia using the Reference Publication Year Spectroscopy - Dayyanah, Dayyanah; Ibrahim, Cecep; Jaya, Asrul (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. Using references in a study as a source of information when conducting research is important. The purpose of this research is to determine the main references used by bibliometric researchers. Research methods. Data gathered from the Scopus database, utilizing Researcher discovery tool by using “bibliometric” as a keyword from 2017-2023, utilizing the bibliometric method with the Reference Publication Year Spectroscopy (RPYS). The stages included data collection, data processing, and data analysis. Data analysis. CRExplorer software was used to import 270 research documents, which was done utilizing all import methodologies including Rstudio biblioshiny software. Results and Discussion. The findings revealed that researchers in Indonesia on bibliometric issue research used references from the European Continent, and East Asia, based on straight count and complete count main reference calculations or references in conducting research. The State University of Surabaya has made the most contributions to bibliometric research in Indonesia, while the Journal of Physics: Conferences Series contains the most publications by Indonesian scholars. Conclusions and recommendations. The references utilised by bibliometric researchers range from 1883 to 2023. To discover references or create citations for bibliometric study, the researchers refer to the main source, which are the researchers of that area.